perancangan pusat kebugaran melalui pendekatan tema curious movement - nurul fatlawi (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Fitness center is a place for doing exercise which make people to be fit and healhty. Recently, urban communities with their activities tend to override healthy lifestyles with a lot of works  without physical activities that affect their health. the design of a fitness center will be a solution for urban communities to balance their lifestyle into a healthy lifestyle. the Curious Movement’s perspective makes the fitness center as a form of movement’s application of activities in sports. The curious movement theme approach to the design of the Fitness Center focuses more on the style, shape, circulation and aesthetics of the building such as the facades and forms that respond to sports fitness activities. The curious movement theme is applied in the design of Fitness Center because getting fit means has to move through the movement of sports activities.